'Authoritarian resilience' as passive revolution: a Gramscian interpretation of counter-revolution in Egypt. Issue 6 (2nd November 2021) - De Smet, Brecht
ABSTRACT: After a renewed scholarly interest in the politics of revolution and societal transformation following the uprisings of 2011, the defeat of the revolutionary tide in the MENA region has drawn attention to the dynamic of counter-revolution and authoritarian resilience. I criticise binary approaches to the process of regime restoration in the region. I argue that 'authoritarian resilience' should be interpreted in terms of Gramsci's concept of 'passive revolution'. I explain that this concept should be used not as a regime typology, but as an analytical 'criterion of interpretation', revealing the capacities and constraints of elites to deflect popular initiative and restructure historical blocs from above. Through the prism of passive revolution 'the regime' appears not as the constant factor, but as one of the forces that constitutes and is constituted by revolutionary struggle. I look concretely at the process of revolution and counter-revolution in Egypt between 2011 and 2013, disentangling the 18 Days of the uprising from the subsequent 'counter-revolution in democratic form' and the coda of the military-led 'counter-revolution from below'.